2005
DOI: 10.1038/nmat1496
|View full text |Cite
|
Sign up to set email alerts
|

Understanding foods as soft materials

Abstract: Foods make up some of the most complex examples of soft condensed matter (SCM) with which we interact daily. Their complexity arises from several factors: the intricacy of components, the different aggregation states in which foods are encountered, and the multitude of relevant characteristic time and length scales. Because foodstuffs are governed by the rules of SCM physics but with all the complications related to real systems, the experimental and theoretical approaches of SCM physics have deepened our comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
498
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 616 publications
(510 citation statements)
references
References 97 publications
11
498
0
1
Order By: Relevance
“…Important progress has in particular been made by drawing analogies between food colloids and colloidal model systems, their interactions and the resulting phase behavior [1]. These issues are of central relevance to food science and technology and have already considerably improved our understanding of food materials.…”
Section: Introductionmentioning
confidence: 99%
“…Important progress has in particular been made by drawing analogies between food colloids and colloidal model systems, their interactions and the resulting phase behavior [1]. These issues are of central relevance to food science and technology and have already considerably improved our understanding of food materials.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, because the geometry is no longer axisymmetric, two area moments of inertia exist (corresponding to the bending modes with respect to the two main symmetry planes of the ribbon), scaling respectively as I ≈ r 0 . (nr 0 ) 3 and I ≈ (r 0 ) 3 . nr 0 .…”
mentioning
confidence: 99%
“…
The aggregation of proteins is central to many aspects of daily life, including food processing, blood coagulation, eye cataract formation disease and prion-related neurodegenerative infections [1][2][3][4][5] . However, the physical mechanisms responsible for amyloidosis-the irreversible fibril formation of various proteins that is linked to disorders such as Alzheimer's, Creutzfeldt-Jakob and Huntington's diseases-have not yet been fully elucidated [6][7][8][9] .
…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, we showed that the parameters obtained from a viscosity model for CM dispersions applied to sets of experimental data from the literature indicate that CM, at high concentrations, behave as soft spheres or microgels (Olivares et al 2013), as also suggested by Mezzenga et al (2005) and Dahbi et al (2010). Also, we showed that the pair interaction energy between CM can be directly obtained from a rheological parameter and it agrees satisfactorily with the values obtained with a previously proposed DLVO-like theory (Tuinier and de Kruif 2002).…”
Section: Introductionmentioning
confidence: 52%